Planar Cell Polarity Pathway Regulates Nephrin Endocytosis in Developing Podocytes - Babayeva, Sima (American Society for Biochemistry and Molecular Biology, 2013)
The noncanonical Wnt/planar cell polarity (PCP) pathway controls a variety of cell behaviors such as polarized protrusive cell activity, directional cell movement, and oriented cell division and is crucial for the normal development of many tissues. Mutations in the PCP genes cause malformation in multiple organs. Recently, the PCP pathway was shown to control endocytosis of PCP and non-PCP proteins necessary for cell shape remodeling and formation of specific junctional protein complexes. During formation of the renal glomerulus, the glomerular capillary becomes enveloped by highly specialized epithelial cells, podocytes, that display unique architecture and are connected via specialized cell-cell junctions (slit diaphragms) that restrict passage of protein into the urine; podocyte differentiation requires active remodeling of cytoskeleton and junctional protein complexes. We report here that in cultured human podocytes, activation of the PCP pathway significantly stimulates endocytosis of the core slit diaphragm protein, nephrin, via a clathrin/β-arrestin-dependent endocytic route. In contrast, depletion of the PCP protein Vangl2 leads to an increase of nephrin at the cell surface; loss of Vangl2 functions in Looptail mice results in disturbed glomerular maturation. We propose that the PCP pathway contributes to podocyte development by regulating nephrin turnover during junctional remodeling as the cells differentiate.